The influence of water channel geometry and proton mobility on the conductivity of Nafion®. (1st October 2016) - Schalenbach, Maximilian; Lueke, Wiebke; Lehnert, Werner; Stolten, Detlef
Abstract: Water uptake of polymer exchange membranes (PEMs) such as Nafion ® leads to water channels that are separated from the solid polymeric phase. In this study, the proton mobility in Nafion ® and the influence of the water channel morphology on its overall conductivity are characterized by experimental approaches in combination with reported computational results. Using impedance spectroscopy with amplitude and frequency variation, the proton mobility was derived to be independent of the length scale of the proton permeation through fully hydrated Nafion ®, suggesting equal direct current (DC) and alternating current (AC) conductivities. The proton conductivities of aqueous solutions with equal proton concentrations as the aqueous phase of fully hydrated Nafion ® membranes were measured to be approximately 6.0 ± 0.7 times higher than those of the membranes. Recently reported resistor network modeling results characterized the influence of the morphology of the aqueous phase on the proton permeation through fully hydrated Nafion ® to approximately the same degree. By comparing these experimental and modeled result, the mean proton mobility in the aqueous phase of fully hydrated Nafion ® was estimated to equal that in aqueous solutions.